Steel water storage tanks: design, construction, maintenance, and repair - Meier, Stephen W. (McGraw-Hill, 2010)
The first comprehensive steel tanks book published in more than a decade Developed by members of the American Water Works Association (AWWA) General Steel Tank Committee, Steel Water Storage Tanks: Design, Construction, Maintenance, and Repair is the most authoritative source of industry information available. This in-depth reference describes the use of steel tanks for potable water storage and includes details on tank sizes, capabilities, styles, construction, appurtenances, site selection, design, operation, maintenance, rehabilitation, inspection, and security.